Viewing urban expansion from below: the complexity of sustainable urban growth - Shaharudin Idrus,; Abdul Samad Hadi ,; Abdul Hadi Harman Shah, (Universiti Kebangsaan Malaysia, 2011)
The approach taken in looking at change influences the understanding of the phenomenon. A pattern of change that seems smooth and linear at a smaller scale might yield fluctuations that can only be perceived at a larger scale, closer to ground zero. Viewing change at the local level can provide tipping points and critical transitions that are hidden in the more general pattern and such detailed incremental approach to urbanisation allows one to understand why, given the same set of drivers, some areas seem to prosper while others lag far behind. This paper views urban expansion as a culmination of local level activities that emerge into a complex network of urban growth. Daily decison making by individuals in the city about owning a house. These decisions eventually produce the spatial-temporal patterns of life in the Malaysian cities. These are then visualised in the patterns of land use, housing spread, commercial and others. These patterns are the outcome of inter-related workings of global capitalism with local ones and the local ‘adat’- the way of life. The article argues that effective planning for the urban expansion needs to be viewed from the local scene. The various local scenarios are then built up incrementally over space and time to produce a region wide explanation of urbanisation. This is, again, an alternate viewing of regional analysis that traditionally looks at the local as merely being a component of the larger region, differentiated by local attributes that create local shifts that skew its share of the regional trend.